61 haplotypes cytb 702 bases in phylip format - Walter, Ryan P.; Roy, Denis; Hussey, Nigel E.; Stelbrink, Björn; Kovacs, Kit M.; Lydersen, Christian; McMeans, Bailey C.; Svavarsson, Jörundur; Kessel, Steven T.; Porsmoguer, Sebastian Biton; Wildes, Sharon; Tribuzio, Cindy A.; et al. (Dryad Digital Repository, 2017)
Phylip file listing 61 haplotypes of partial reads of the mtDNA cytochrome b gene used in Walter et al., The first 22 haplotypes originally published in Murray et al. (2008 - Mar Biol): H1-H22. Eight haplotypes reported in Hussey et al. (2015 - Polar Biol): H28 H38 H41 H43 H46, H48, H50, H53. all other recovered as novel sequences in Walter et al.